2001
DOI: 10.1002/hed.1108.abs
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of retromolar trigone: Long‐term radiation therapy outcome

Abstract: Background. Cancer of the retromolar trigone is an uncommon head and neck cancer. In this retrospective study, we identified the prognostic factors and evaluated the therapeutic outcomes of patients treated with preoperative radiation therapy (RT), postoperative RT, and RT alone.Methods. Between 1971 and 1994, 65 patients with histologically proven epidermoid carcinoma of the retromolar trigone were treated at the Mallinckrodt Institute of Radiology; 10 patients received preoperative RT (30-55.2 Gy), 39 recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…The tumor spreads to the anterior pillar in 80% to 84.5% of the cases and the majority of them invade 3 or more subsites of the oral cavity and oropharynx. [8][9][10] Despite this tendency to spread to the anterior pillar, the majority of the authors study these subsites separately. In fact, RMT cancer is more prone to bone invasion because of its close proximity to the mandible and the maxilla.…”
Section: Primary Site Localizationmentioning
confidence: 96%
See 3 more Smart Citations
“…The tumor spreads to the anterior pillar in 80% to 84.5% of the cases and the majority of them invade 3 or more subsites of the oral cavity and oropharynx. [8][9][10] Despite this tendency to spread to the anterior pillar, the majority of the authors study these subsites separately. In fact, RMT cancer is more prone to bone invasion because of its close proximity to the mandible and the maxilla.…”
Section: Primary Site Localizationmentioning
confidence: 96%
“…Out of 14 studies published on RMT cancer treatment in the English-language literature between 1959 and 2007, only 6 of them compared 2 or more treatment modalities. 1,9,10,15,27,28 In the other studies, patients receive 1 treatment modality (surgery or radiation therapy) and the results are compared to historical series. However, patient and tumor characteristics are not comparable between these studies, and the reported outcomes are not uniform.…”
Section: Unimodal Treatment or Combined Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Primary retromolar trigone (RMT) SCC, though less frequently observed (5.6% vs. 45.2% oral tongue SCC), poses a unique challenge to surgeons, as early mandibular invasion and regional metastases are not uncommon . Factors complicating management are extension to the buccal mucosa, tonsillar pillar, and soft palate …”
Section: Introductionmentioning
confidence: 99%